Evaluation of Antitrypanosomal Activity of Tetracycline in Animal Model - Rufa’i, F.A.; Mukhtar, M.D. (International Journal of Scientific Research in Biological Sciences, 2022)
Trypanosomiasis remains a disease with unsatisfactory medical control. To date, its chemotherapy relies on suramin, pentamidine, melarsoprol and eflornithine. Each of these drugs is expensive, laborious to administer, lacks efficacy against some trypanosomes species and lead to some significant side effects. This study aimed to evaluate the Antitrypanosomal activity of Tetracycline in animal model. A total of 12 adult rats, 7 weeks old of both sexes were randomly divided into six groups (1, 2,3,4,5 and 6) of 2 animals each. All the Groups (1-6) were intraperitoneally infected with 0.1 ml of blood containing the parasites. Groups 1-4 received the tetracycline intraperitoneally at daily doses of 0.01, 0.1, 1.0 and 10mg/ml/kg body weight respectively, while Group 5 received standard Trypanosomal drug of 7.86mg/kg (suramin dose) which served as the Positive control and Group 6 was infected without any treatment (Negative control). Physiological, Physical and Behavioral Changes as well as Hematological parameters were all evaluated. There was decreased in the level of parasitaemia, decrease from higher to normal body temperature, increases in body weight and survival rate, as well as low pallor of the mucus membrane, loss of condition, pyrexia, lacrimation and aggression with high food consumption in all the tetracycline treated groups. More so, a significant decrease in mean PCV, Hgb, RBC, MCV, MCH and MCHC in all the treated groups often comparing with suramin treated group P-value <0.05. It was concluded that, Tetracycline can be considered as potent Antitrypanosomal agent and can be used in the treatment of trypanosomiasis.